Effect of Wu Zhi San supplementation in LPS-induced intestinal inflammation and barrier damage in broilers - Sun, Han; Zheng, Xirui; Yang, Bowen; Yan, Mingen; Wang, Huiting; Yang, Shijing; Shi, Dayou; Guo, Shining; Liu, Cui (Frontiers in Veterinary Science, 2023)
Intestinal inflammation and barrier damage can inhibit the absorption and transportation of nutrients in the small intestine, and lead to various chronic diseases. Wu Zhi San (WZS) is a traditional Chinese formula composed of Schisandrae, Anemarrhenae, Lonicerae and Glycyrrhizae which was made to cure intestinal inflammation and barrier damage in Broilers. To evaluate the protective effect of WZS on intestinal inflammation and barrier damage of broilers under lipopolysaccharide (LPS) stress, a total two hundred one-day-old broilers were randomly divided into 5 groups. They were CON group, LPS group and WZS group (WZS-H, WZS-M, WZS-L) respectively, and were designed for stress phase I (days 15, 17, 19, and 21) and stress phase II (days 29, 31, 33, and 35). The protective effect of WZS on intestinal tract was evaluated by measuring the levels of serum MPO, DAO, SOD, D-LA and the expression of inflammatory factors in jejunum. The results showed that the diet supplemented with WZS could significantly reduced serum MPO, DAO, D-LA levels and This is a provisional file, not the final typeset article jejunal CD in broilers (P<0.05) and increased serum SOD levels and jejunal VH (P<0.05), significantly down-regulated the expression of NF-κB, TLR4, MyD88 and inflammatory cytokines (TNF-α, IL-1β, IL-6 and IL-10), and upregulated Claudin-1, Occludin-1, and ZO-1 in broiler jejunum mucosa (P<0.05). On the other hand, WZS could significantly reduced the protein expression of NF-κB (p65) in broiler jejunum (P<0.05). These results indicate that supplementing WZS in the diet can reduce intestinal inflammation and alleviate intestinal barrier damage, and by inhibiting NF-κB/TLR4/MyD88 signaling pathway intervenes in LPS induced stress injury in broilers.